2019
DOI: 10.1016/j.molp.2019.01.018
|View full text |Cite
|
Sign up to set email alerts
|

A Phytophthora capsici Effector Targets ACD11 Binding Partners that Regulate ROS-Mediated Defense Response in Arabidopsis

Abstract: Reactive oxygen species (ROS) play a vital role in plant immune response, but the genes involved in the regulation of ROS are scantily reported. Phytophthora pathogens produce a large number of effectors to promote infection, but the modes of action adopted are largely unknown. Here, we report that RxLR207 could activate ROS-mediated cell death in Nicotiana benthamiana and was essential for virulence of P. capsici. We found that this effector targeted BPA1 (binding partner of ACD11) and four members of BPLs (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 111 publications
(119 citation statements)
references
References 82 publications
3
115
0
1
Order By: Relevance
“…In P. sojae , early-induced RXLRs inhibit host cell death triggered by PAMPs, while necrosis is caused by late-induced RXLR effectors [31]. Another Phytophthora pathogen, P. capsici , secretes a RXLR effector to induce host defense and cell death, and trigger the biotroph-to-necrotroph transition [9]. Since most Pythium pathogens are necrotrophic, their RXLRs may trigger host cell death instead of acting as cell death repressors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In P. sojae , early-induced RXLRs inhibit host cell death triggered by PAMPs, while necrosis is caused by late-induced RXLR effectors [31]. Another Phytophthora pathogen, P. capsici , secretes a RXLR effector to induce host defense and cell death, and trigger the biotroph-to-necrotroph transition [9]. Since most Pythium pathogens are necrotrophic, their RXLRs may trigger host cell death instead of acting as cell death repressors.…”
Section: Discussionmentioning
confidence: 99%
“…PsAvh262, which is essential for the pathogenicity of Phytophthora sojae , suppresses ER stress-dependent immunity via stabilizing ER-luminal binding immunoglobulin proteins (BiPs) [8]. A Phytophthora capsici RXLR effector, PcRXLR207, triggers the degradation of BPA1 (Binding partner of ACD11) family proteins to facilitate the biotroph to necrotroph transition [9]. A conserved RXLR effector HaRxL23 from Hyaloperonospora arabidopsidis can suppress PTI in tobacco as well as effector-triggered immunity (ETI) in soybean [10].…”
Section: Introductionmentioning
confidence: 99%
“…EDS1 plays an important role in basal resistance and ETI-/SAmediated defence response, while BAK1 (BRI1-associated kinase 1) and BIK1 (Botrytis-induced kinase 1) are core components in the PTI signalling pathway (Lin et al, 2014;Cui et al, 2017). To investigate whether P. capsici secretes effectors that target plant EDS1, BAK1, and BIK1, 42 RxLR effectors (Lamour et al, 2012a) were separately cloned into prey vector and screened for interactors of EDS1, BAK1, and BIK1 using the Y2H approach (Li et al, 2019a, Table S1). Results showed that one effector, PcAvh103, was repeatedly identified from two independent screens (Table S1).…”
Section: Pcavh103 Interacts With Eds1mentioning
confidence: 99%
“…In addition, P. sojae effector PSR1 directly targets host PINP1, which is a previously unidentified component of RNA silencing, to promote infection (Qiao et al, 2015). More recently, P. capsici effector RxLR207 can regulate ROS-mediated defence response to promote the transition from the biotrophic to the necrotrophic stage by targeting Arabidopsis BPA1 (binding partner of ACD11) and BPLs (BPA1-Like proteins) (Li et al, 2019a). In our study, we found expression of PcAvh103 significantly promotes leaf colonization of P. capsici and demonstrated that PcAvh103 contributes to P. capsici virulence through targeting EDS1 in leaves.…”
Section: Pcavh103 Can Disrupt Eds1-pad4 Associationmentioning
confidence: 99%
“…Interestingly, CPK28 also modulates vegetative stage transition via tissue-specific balancing of jasmonic acid (JA) and gibberellic acid (GA) (Matschi et al 2015). We recently reported that the Arabidopsis binding partner 1 of accelerated cell death 11 (ACD11) (BPA1) and BPA1-like homologs are novel regulators of ROS accumulation and cell death under biotic stresses (Li et al 2019).…”
Section: Introductionmentioning
confidence: 99%